Palynofacies Analysis of the Eocene Bayah Formation in Bayah High, Banten Block, SW Java - Bob Yuris Chandra; A.T. Rahardjo; Dardji Noeradi (Ikatan Ahli Geologi Indonesia, 2014)
The objective of this study is to characterize the palynofacies of the Bayah Formation from cores of wells DDH-1 (242m) and DDH-2 (315m).The wells were systematically sampled at 5m intervals. There were 47 samples from the DDH-1 and 62 samples from the DDH-2 wells. Sediment preparation was done in the Palynology Laboratory, Geological Engineering of ITB Laboratory. The examination of the processed samples was carried out with a light microscope at 400X magnification. The results of palynofacies investigation are presented in the form of palynodebris diagrams, which were then used for the basic interpretation. The palynodebris character of the Bayah Formation at DDH-1 core can be grouped into 6 palynofacies units, DDH-2 core into 7 palynofacies units. Palynofacies units 1 to 4 showed similar successions and can be correlated. The datum of the palynofacies correlation was the acme zone of Proxapertites operculatus, which is present in both wells.